The emperor - Teevan, Colin (Oberon modern plays., 2016)
The Emperor tells the story of the downfall of Emperor Haile Selassie I of Ethiopia and with it the end of a threethousand- year-old monarchy that traced its origins back to King Solomon. Based on the extraordinary book by legendary Polish journalist Ryszard Kapuściński, it is told from the unique perspective of the Emperor's former servants, courtiers and ministers. It is a powerful exploration of the nature of power and loyalty. This adaptation and production is from the adaptor and the team that created the international hit Kafka's Monkey which also starred the master of transformation, Kathryn Hunter.